Association of physical activity in green space, dietary pattern and child obesity - Andrew, Dogara Victor (2017)
Over the past three decades, obesity rates affecting children in Malaysia have been rising rapidly thereby presenting a major public health concern. However green spaces have been seen as an effective environmental component that improves the quality of life. Hence, physical activity in green space and healthy dietary patterns may reduce the risk of obesity. In this guise, this study aims to empirically evaluate the diet and physical activity pattern of the children between the ages 6-12, determine their obesity levels after the first phase and the second phase and investigate the association of diet and physical activity on the body mass index (BMI) of the respondents after the first and second phase respectively. The research utilize a quantitative experimental study design, and the instruments used for the research is the questionnaire which collects demographic information of the respondents. A researcher’s checklist was used to record measurement of height and weight and calculates the BMI of the respondent. Also, a daily physical activity checklist which records the respondents frequency of visits to green space, time spent in green space, and the type of physical activity performed in green space and lastly a diet pattern checklist which records the type of food, fruits, snacks, drinks, the place eaten and the portion sizes of those for every meal of the respondents. Scores were imputed in to SPSS version 21 to evaluate physical activity in green space and diet pattern using descriptive statistics, the level of BMI of the respondents were analyze using paired sample t-test and linear regression model was used to analyze the association of diet and physical activity on the respondents BMI. A total of 12 respondents participated in the first, second and third phase of the experiment for 180 days respectively. However 3 respondents later withdraw from participating in the experiment. Nonetheless, the findings show that there was significant decrease in the level of BMI before and after the study. However, vigorous physical activity was found to be associated with bmi at the first, second and third phase while moderate physical activity and time spent on green space was found to be associated with the respondent’s bmi at the second and third phase of the study respectively. In addition, the result shows that fruits were associated with the respondent’s bmi at breakfast, lunch, and diner at all phases of the study while drinks were found to be associated with bmi at all meals and at all phases of the study with food and snacks associated with the respondents bmi only at dinner and breakfast for second and third phase respectively. To reduce the rising prevalence of obesity, parent should ensure that their children participate in frequent moderate to vigorous physical activity and should also encourage the intake of more fruits and water along their meals.